Effect of ω-3 fatty acid supplementation on endothelial function, endogenous fibrinolysis and platelet activation in patients with a previous myocardial infarction: a randomised controlled trial. Issue 9 (25th September 2013) - Din, Jehangir N; Sarma, Jaydeep; Harding, Scott A; Lyall, Karin; Newby, David E; Flapan, Andrew D
Abstract : Objective: The mechanisms through which ω-3 fatty acids reduce adverse cardiac events remain uncertain. We aimed to investigate the effect of ω-3 fatty acid supplementation on endothelial vasomotor function, endogenous fibrinolysis, and platelet and monocyte activation in patients with coronary heart disease. Design: Randomised, double-blind, placebo-controlled, cross-over trial. Setting: Academic cardiac centre. Participants: 20 male patients with a previous myocardial infarction. Intervention: ω-3 Fatty acid supplementation (2 g/day for 6 weeks) versus olive oil placebo. Outcome measures: Peripheral blood was taken for analysis of platelet and monocyte activation, and forearm blood flow (FBF) was assessed in a subset of 12 patients during intrabrachial infusions of acetylcholine, substance P and sodium nitroprusside. Stimulated plasma tissue plasminogen activator (t-PA) concentrations were measured during substance P infusion. Results: All vasodilators caused dose-dependent increases in FBF (p<0.0001). ω-3 Fatty acid supplementation did not affect endothelium-dependent vasodilation with acetylcholine and substance P compared with placebo (p=0.5 and 0.9). Substance P caused a dose-dependent increase in plasma t-PA concentrations (p<0.0001), which was not affected by ω-3 fatty acid supplementation (p=0.9). ω-3 Fatty acids did not affect platelet–monocyte aggregation, platelet P-selectin or CD40L, or monocyte CD40. Conclusions: We have demonstrated that dietary supplementation with ω-3 fatty acids does not affect endothelial vasomotor function, endothelial t-PA release, or platelet and monocyte activation in patients with coronary heart disease. Cardiac benefits conferred by ω-3 fatty acids in coronary heart disease are unlikely to be mediated through effects on these systems.